Impact of load on the knee in relation to a treadmill angle - Fikret Veljović; Edin Begić; Avdo Voloder; Reuf Karabeg; Amer Iglica; Nedim Begić; Alden Begić; Adisa Chikha (Medicinski glasnik, 2020)
Aim: To determine the effect of the load on the meniscus in relation to a different angle, and to present the impact of force on eventual injury of menisci. Methods: Research included 200 males with average height of 178.5 cm, mass 83.5 kg, and average age of 22 years. The simulation of treadmill that was used in the evaluation of ischemic heart disease was made. Effects on the knee were evaluated by measuring at different inclinations (5°70’, 6°80’, 7°90’, 9°10’, 10°20’, 11°30’ and 12°40’). Results: With increasing ascent of treadmill the load on the meniscus also increased. Each increase in ascent after 22% (which corresponded to the angle of 12°40’ and seventh degree of load according to the Bruce protocol) at given anthropological values was an etiological factor for meniscus injury. Conclusion: The seventh degree of load according to the Bruce protocol can lead to the meniscus injury.
Keywords: computer simulation; injuries; mechanics; meniscus